2018
DOI: 10.1016/j.jped.2017.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Advanced bone age as an indicator facilitates the diagnosis of precocious puberty

Abstract: According to the statistical analysis, advanced bone age is the most effective predictor of the result of luteinizing hormone-releasing hormone stimulation test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Secondly, "BA-CA" was the second-top rank feature. Although premature adrenarche is often associated with BA-CA � 2 years [35], a recent study reported that BA-CA was the most effective predictor of positive response to the GnRHa stimulation test [36]. We found that girls with CPP presented with greater BA-CA than those without CPP, in line with previous findings [36,37].…”
Section: Plos Onesupporting
confidence: 91%
See 1 more Smart Citation
“…Secondly, "BA-CA" was the second-top rank feature. Although premature adrenarche is often associated with BA-CA � 2 years [35], a recent study reported that BA-CA was the most effective predictor of positive response to the GnRHa stimulation test [36]. We found that girls with CPP presented with greater BA-CA than those without CPP, in line with previous findings [36,37].…”
Section: Plos Onesupporting
confidence: 91%
“…Although premature adrenarche is often associated with BA-CA � 2 years [35], a recent study reported that BA-CA was the most effective predictor of positive response to the GnRHa stimulation test [36]. We found that girls with CPP presented with greater BA-CA than those without CPP, in line with previous findings [36,37]. LIME analysis revealed that girls with a "BA-CA" of > 2.13 years were at high risk for CPP in both populations, whereas a "BA-CA" of < 1.16 years helped exclude CPP diagnosis.…”
Section: Plos Onementioning
confidence: 99%
“…Suh et al [10] found that accelerated growth rate, advanced bone age, and increased basal gonadotropin and insulin-like growth factor-I (IGF-I) levels were correlated with CPP. Traditional statistical analysis including t test and binary logistic regression were used to select factors correlated with the GnRH test [11-14]. Although remarkable progress has been made in these studies, there is a long way to go for their application in clinics due to the low sensitivity or specificity of tests.…”
Section: Introductionmentioning
confidence: 99%
“…It also plays a role in making-decision for treatment. Moreover, in a study, it was demonstrated that advanced bone age is the most effective predictor of the result of GnRH test (32). This indicates that advanced bone age can be used as an alternative diagnostic tool to GnRH test.…”
Section: Discussionmentioning
confidence: 95%